Relationship between peripheral blood miR-146b-5p levels and lymphocyte subsets in patients with sepsis and its predictive value for prognosis: a single-center study - Cheng, Sha; Wang, Jiaojiao; Wang, Pengfei; Long, Xianli; Liu, Huiling; Li, Xueyin; Zhang, Xiaowei; Zhao, Xuemei; Sun, Hang; Wu, Chuanxin (Frontiers in Immunology, 2025)
BackgroundSepsis is a life-threatening disease with challenges in clinical management due to delayed diagnosis and immunosuppression. Lymphopenia is a key prognostic indicator in sepsis. microRNAs (miRNAs) are recognized as key immune modulators affecting all stages of inflammation. In this study, we investigated the expression of miR-146b-5p and lymphocyte subsets in sepsis patients and analyzed their correlation with the aim of establishing their combined predictive value for clinical outcomes and advancing personalized treatment strategies.MethodsFrom January 2020 to July 2024, we enrolled 191 patients diagnosed with sepsis at the ICU of the Second Affiliated Hospital of Chongqing Medical University and collected basic clinical data. These patients were categorized into two groups: nonsurvivors (n = 117) and survivors (n = 74). Correlation analysis was employed to analyze the correlation between miR-146b-5p and lymphocyte subsets with disease severity. Binary logistic regression and Cox regression analyses were employed to identify independent risk factors influencing the prognosis of sepsis. The predictive value of miR-146b-5p and lymphocyte subsets for sepsis prognosis was assessed using receiver operating characteristic (ROC) curves.ResultsmiR-146b-5p expression was significantly lower in sepsis patients compared to HD group, with levels in the nonsurvivor group being lower than those in the survivor group. Survival curves for miR-146b-5p indicated that lower levels of miR-146b-5p (<0.272) were associated with a higher mortality rate (HR 3.063). The absolute counts of lymphocytes (Lym), CD3+ T cells, CD4+ T cells, and CD8+ T cells were significantly lower in the sepsis group compared to the HD group. Testing lymphocyte counts at different time points revealed that absolute counts of CD3+ T cells, CD4+ T cells, and CD8+ T cells were consistently lower in the sepsis group across all time intervals. miR-146b-5p levels were predictive of patient prognosis, with the combination of miR-146b-5p and APACHE II scores yielding the highest AUC.ConclusionThe early-stage sepsis-associated downregulation of miR-146b-5p serves as a promising biomarker for severity stratification and prognostic evaluation. The combination of miR-146b-5p with APACHE II scores enhances diagnostic accuracy. Additionally, dynamic monitoring of lymphocyte subsets may facilitate the evaluation of immune status and guide personalized treatment strategies.